2012
DOI: 10.1073/pnas.1116971109
|View full text |Cite
|
Sign up to set email alerts
|

Amorfrutins are potent antidiabetic dietary natural products

Abstract: Given worldwide increases in the incidence of obesity and type 2 diabetes, new strategies for preventing and treating metabolic diseases are needed. The nuclear receptor PPARγ (peroxisome proliferator-activated receptor gamma) plays a central role in lipid and glucose metabolism; however, current PPARγ-targeting drugs are characterized by undesirable side effects. Natural products from edible biomaterial provide a structurally diverse resource to alleviate complex disorders via tailored nutritional interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
261
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 178 publications
(268 citation statements)
references
References 39 publications
6
261
0
1
Order By: Relevance
“…Mouse studies conclude that BVC displays properties desired for a glucoselowering pan-PPAR agonist. Previous studies have indicated that full agonism of PPAR-γ, as with RSG and PGZ, may be responsible for the side effects associated with glucoselowering effects [37][38][39]. Therefore, BVC does not cause weight gain and hepatotoxicity because of its submaximal activation of PPAR-γ and additional activation of PPAR-α and -β/δ.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse studies conclude that BVC displays properties desired for a glucoselowering pan-PPAR agonist. Previous studies have indicated that full agonism of PPAR-γ, as with RSG and PGZ, may be responsible for the side effects associated with glucoselowering effects [37][38][39]. Therefore, BVC does not cause weight gain and hepatotoxicity because of its submaximal activation of PPAR-γ and additional activation of PPAR-α and -β/δ.…”
Section: Discussionmentioning
confidence: 99%
“…11 Recently this family of natural products has been discovered to exhibit antidiabetic activities. 12 More specifically, amorfrutin B was identified as a partial agonist of peroxisome proliferator-activated receptor γ (PPARγ) with a considerably higher affinity and γ-selectivity than that of any other amorfrutins previously reported, and similar to that of the marketed drug rosiglitazone. 13 Due to its physiological profiles remarkably different from current marketed PPARγ drugs, and the predictable application prospects, this compound has found extensive research interest in many labs, for example, in pharmacodynamic and structure-activity relationship studies.…”
Section: Introductionmentioning
confidence: 99%
“…12 The geranyl moiety could be introduced by electrophilic aromatic alkylation with geraniol in the presence of BF 3 -OEt 2 as catalyst or by using regioselective metalation of the 2-position with n-BuLi or KH and subsequent alkylation with geranyl bromide or chloride. 13,15,18 However, yields were typically low, with co-production of considerable amounts of O-geranylated product.…”
Section: Introductionmentioning
confidence: 99%
“…It was not surprising if there are many significant research efforts to explore the PPAR-γ activating potential of a wide range of natural products originating from medicinal plants. (53) PPAR-γ-ligands used to often identified in plants that are common food sources, including the tea plant, soybeans, palm oil, ginger, and grapes. The presence of PPAR-γ ligands in food products warrants an exploration whether this nuclear receptor may be effectively activated by the intake of nutraceuticals, by consumption of functional foods or by dietary supplements.…”
Section: Ppar-γ In Autoimmune Diseasementioning
confidence: 99%